Asesmen Diri Pada Usaha Mikro Kecil dan Menengah (UMKM) Batik Semarangan - , Dina Christina Yuliarti; , Bayu Sutikno, SE., MSM., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Batik semarangan, whose production had stopped for several decades after the War of Independence, 1945, are now produced again by several SMEs in Semarang, Central Java Province. The business activity is supported by Semarang City Government who have provided assistance in each batik training event and exhibition. The government has projected Kampung Batik Gedong as a center of batik semarangan. However, these efforts seem to succeeded yet because batik semarangan SMEs has not shown the maximum business performance. The main objective of this study was to analyze the managerial aspects that need to be prioritized in business performance improvement plan of batik semarangan SMEs through self-assessment method. Self-assessment is an evaluation method used to make continuous improvements in the concept of Total Quality Management (TQM). Through self-assessment, an organization can identify their strengths and aspects for improvement. Self-assessment is usually employed by large companies, but rarely found in small micro and medium enterprises. Self-assessment tools used in this research is an adaption and combination of the European Foundation for Quality Management (EFQM) Excellence Model and Trafford Park Small Business Evaluation and Support Service (TPSBESS) Model. Observed variables consist of 9 items, i.e. (1) leadership, (2) strategy, (3) human resources, (4) partnerships and resources, (5) processes, products, and services, (6) customers and market, (7) society, (8) key performance results, and (9) regulation. Data is obtained through survey by distributing questionnaires to six respondents. Respondents of this research are the owners or managers of SMEs. Data analysis is done in three ways: analysis of each variable, analysis of each company, and cross tabulation analysis. Analysis of each variable is done through descriptive approach, based on the average value. Analysis of each company is done by comparing self-assessment results to observation made by researcher. The cross tabulation analysis is done through descriptive approach, based on frequency distributions of each variable. Self-assessment results showed that regulation, leadership, and partnerships and resources rank first, second, and third in priority of improvements. The researcher observed that most respondents do not pay attention to external aspects, particularly environmental issues, image of responsible organization, and legal implications of day-to-day business operations.